2018
DOI: 10.1111/apt.14604
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ledipasvir/sofosbuvir with or without ribavirin in hepatitis C genotype 1 patients including those with decompensated cirrhosis who failed prior treatment with simeprevir/sofosbuvir

Abstract: Single tablet fixed-dose combination LDV/SOF ± RBV is efficacious and well tolerated in patients who previously failed treatment with SIM/SOF, including those with decompensated cirrhosis and recurrent hepatitis C following liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Most published data have focused on retreatment of patients who failed one IFN‐free DAA therapy. The 21% failure rate in the present study is in the range of that reported in other studies . Before controlled trials with SOF/VEL/VOX and G/P have become available the evidence for retreatment of patients who had failed IFN‐free DAA therapy was based on GT1 patients retreated with SOF/LDV plus RBV for 12 to 24 weeks after relapse to SOF containing IFN‐free regimens in clinical trials .…”
Section: Discussionsupporting
confidence: 64%
“…Most published data have focused on retreatment of patients who failed one IFN‐free DAA therapy. The 21% failure rate in the present study is in the range of that reported in other studies . Before controlled trials with SOF/VEL/VOX and G/P have become available the evidence for retreatment of patients who had failed IFN‐free DAA therapy was based on GT1 patients retreated with SOF/LDV plus RBV for 12 to 24 weeks after relapse to SOF containing IFN‐free regimens in clinical trials .…”
Section: Discussionsupporting
confidence: 64%
“…They included a relatively large population of genotype 1 patients who did not respond to sofosbuvir + simeprevir. Of note, they confirm that switching from a protease inhibitor (simeprevir) to a NS5A‐inhibitor (ledipasvir) might be sufficient in the majority of these patients reaching a similar efficacy as reported for boceprevir‐ and telaprevir‐experienced patients . Their results are even more impressive when considering that 87% of the study cohort had liver cirrhosis .…”
supporting
confidence: 68%
“…Of note, they confirm that switching from a protease inhibitor (simeprevir) to a NS5A‐inhibitor (ledipasvir) might be sufficient in the majority of these patients reaching a similar efficacy as reported for boceprevir‐ and telaprevir‐experienced patients . Their results are even more impressive when considering that 87% of the study cohort had liver cirrhosis . Most recently, the fixed dose combination of sofosbuvir, velpatasvir and voxilaprevir has been approved for retreatment of DAA failures in the USA and Europe.…”
supporting
confidence: 62%
See 2 more Smart Citations